STRATEGI PEMBENTUKAN SIKAP DISPLIN DAN MANDIRI PADA PEMBELAJARAN TEMATIK MUATAN ILMU PENGETAHUAN SOSIAL SISWA KELAS V SD N PUSMALANG - Ayu Puspitasari, Dyah; Wardhani, Kristi (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2021)
This study aims to 1) describe the process of implementing the thematic learning of social science content, 2) describe the obstacles and efforts to overcome the teacher in shaping the character of disciplined and independent attitudes through thematic learning of social science content 3) describe the strategy of forming the character of the disciplined attitude and independent through thematic learning of social science content. This research was conducted from February to June 2021 in class V SD Negeri Pusmalang, Cangkringan District, Sleman Regency. This research is descriptive qualitative research. The primary data sources were the principal, fifth-grade teacher, three fifth-grade students. The technique of collecting research data was through observation, interviews, and documentation. Test the validity of the data source triangulation, technique triangulation, time triangulation. The data analysis technique of this study used the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of this study are descriptive: (1) The thematic learning process of social science content can take place well according to the 2013 Curriculum containing the formation of disciplined and independent attitudes (2) Barriers and efforts of teachers do not understand and have not optimized the formation of attitudes, students are not ready to take part in learning resulting in the transfer of value is not optimal. Efforts to overcome these factors, principals aggressively remind teachers of the importance of forming students' self-disciplined attitudes, teachers in overcoming inhibiting factors from students building good communication (3) Teachers' strategies for forming disciplined and independent attitudes through thematic learning of social science content using the reward and punishment method, teachers build good communication, model approach, socialization to students and parents.